Malaysian consumers’ acceptance of natural and synthetic functional food - Phuah, Kit Teng (2014)
The concept of functional food is not new to the Malaysian people as traditional medicines have made tremendous contributions over the past centuries. However, with the advent of the pharmaceutical technology and industry some of the remedial formulas for alternative food and medicines have been forgotten, thus paving the way for the consumption of synthetic functional food. The growth of the economy together with the strong desire among the Malaysian consumers to maintain a healthy lifestyle and their growing awareness of functional ingredients are the driving force in the functional food and beverage market of the country. Although the consumption of natural and synthetic functional food is increasing in Malaysia, relatively little is known about how consumers perceive these products or about which factors are affecting their acceptance. Therefore, to gain success in the functional food market, all firms involved in the food industry need to explore the consumers’ intention in accepting foods containing natural or synthetic compounds and the reasons behind including these products in their daily diet. Thus the objective of this study is to determine the Malaysian consumers’ intention in accepting natural and synthetic functional food. A survey was conducted from 28 April 2013 until 15 October 2013 where 2004 Malaysian households were interviewed through structured questionnaires. The Theory of Planned Behavior and Health Belief Model are adopted and modified for this study. Descriptive statistics, exploratory factor analysis and structural equation modeling are used to analyze the collected data. The results indicate that half of the respondents are not familiar and could not differentiate between natural and synthetic functional food since they are not well differentiated in Malaysia. A high proportion of the respondents believe that functional food is medical food, followed by it being a conventional food, a type of food for special dietary use, a modified food and a nutraceutical food. Only a quarter of the respondents expressed that they always buy functional foods because they want to stay healthy, to avoid medical conditions or to stay attractive. However, the result shows that the majority of the respondents prefer to consume natural functional food than synthetic ones. Based on the exploratory factor analysis, five factors are identified that influence consumers’ intention in accepting natural functional foods. These factors are perceived susceptibility, perceived barriers, consumer attitude, subjective norms and perceived benefits of natural functional food. However, seven factors are identified that can influence consumers’ intention in accepting synthetic functional food such as perceived susceptibility, perceived barriers, consumer attitude, subjective norms, perceived benefits, perceived behavioral control and perceived severity. Furthermore, the result of structural equation modeling shows that the data set was normal, valid and reliable. The result for natural functional food shows that attitude has a partial mediating effect on perceived barriers, perceived susceptibility and perceived benefits which influence consumers’ intention in accepting natural functional food. However, it is also found that attitude has no mediation effect on the subjective norms of the consumers to form the intention of accepting natural functional food. In other words, subjective norms have a direct influence on consumers’ intention to accept natural functional food. On the other hand, the result for synthetic functional food shows that attitude has a fully mediating effect on subjective norms to form consumers’ intention in accepting synthetic functional foods. However, attitude has an indirect effect on perceived barriers, perceived susceptibility and perceived behavioral control to form consumers’ intention in accepting synthetic functional foods. Consumer attitude will also partially affect perceived benefits and there is no mediation effect on perceived severity of consumers’ intention in accepting synthetic functional food. Moreover, the result of the structural equation modeling also shows that there is some form of moderating effect of gender, marital status, age, education level and income level on the overall model. Functional food is becoming increasing important for the food industry particularly in Malaysia. To succeed in the functional food markets domestically or internationally, manufacturers or marketers should understand and obtain more profound information on the consumers’ behavior and demands. Marketing strategies for natural and synthetic functional food must take into consideration market segmentation as each product has its own niche market. The policy should clearly provide an opportunity for the producers and manufacturer of such products to communicate the evident medical and health benefits of consuming natural and synthetic functional foods with each other and the public in general. Therefore, an international definition for functional foods should be adopted by governments or related institutions so that the consumers can differentiate between functional food and other types of food products.